The Role of Bifidobacteria in Predictive and Preventive Medicine: A Focus on Eczema and Hypercholesterolemia - Luisa Marras; Michele Caputo; Sonia Bisicchia; Matteo Soato; Giacomo Bertolino; Susanna Vaccaro; Rosanna Inturri (Microorganisms, 2021)
Bifidobacteria colonize the human gastrointestinal tract early on in life, their interaction with the host starting soon after birth. The health benefits are strain specific and could be due to the produced polysaccharides. The consumption of probiotics may prevent obesity, irritable bowel syndrome, eczema or atopic dermatitis, and asthma. Non-replicative strains of Bifidobacterium longum (NCC3001 and NCC2705) promote the differentiation of normal human epidermal keratinocytes (NHEKs), inducing a high expression of differentiation markers (keratin —KRT1—, and transglutaminase —TGM1—) and pro-regeneration markers (cathepsins), including β-defensin-1, which plays an important role in modulating the cutaneous immune response. Strains belonging to the genera Bifidobacterium and Lactobacillus can increase tight-junction proteins in NHEKs and enhance barrier function. Bifidobacteria and lactobacilli may be used as prophylactic or therapeutic agents towards enteric pathogens, antibiotic-associated diarrhea, lactose intolerance, ulcerative colitis, irritable bowel syndrome, colorectal cancer, cholesterol reduction, and control of obesity and metabolic disorders. Bifidobacterium bifidum showed an in vitro capability of lowering cholesterol levels thanks to its absorption into the bacterial membrane. Several strains of the species Lactobacillus acidophilus, L. delbrueckii subsp. bulgaricus, L. casei, and L. gasseri led to a reduced amount of serum cholesterol due to their ability to assimilate cholesterol (in vitro). Lactococcus lactis KF147 and Lactobacillus plantarum Lp81 have also been shown to reduce cholesterol levels by 12%. Clarifying the specific health mechanisms of Bifidobacterium and Lactobacillus strains in preventing high-cost pathologies could be useful for delineating effective guidelines for the treatment of infants and adults.